Scientific and technological applications of the derivative and integral using computer simulation (Research, Society and Development, 2022)
Humanity is going through a technological movement never seen before, in which information and communication reach an essential level in people's lives. Among the technological innovations, computer simulations stand out, which can be conceptualized as the construction and operational manipulation of a model, that is, a physical or symbolic representation of aspects of a physical or social process. Simulations are composed of an arrangement of several numerical schemes dedicated to solving specific problems, such as: solving algebraic equations, solving systems of linear equations, interpolating and fitting points, calculating derivatives and integrals, solving ordinary differential equations, or even real problems. In this context, the present research aims to perform a literature review on scientific and technological applications of the derivative and integral using computer simulation, from an exploratory and bibliographic study. It was verified that the objective of the work was met, considering that four studies were presented that verified diverse applications, such as: three-dimensional flows, surface runoff, wave interference, problems in Finance, Engineering and Statistics.